Adverse feedback loop in the bank-based financial systems - Adam Geršl; Petr Jakubík (Charles University in Prague, Institute of Economic Studies (IES), 2010)
This paper examines procyclicality of the financial system. The introduction describes the natural and regulatory sources of procyclicality, focusing on the potential procyclical effect of the current Basel II regulatory framework for banks. It also mentions the regulatory tools for mitigating procyclical behaviour by financial institutions currently being discussed in international forums. Under certain conditions, procyclical behaviour of the banking sector can lead to an adverse feedback loop whereby banks, in response to an economic downswing, engage in deleveraging and reduce their lending to the economy in order to maintain the required capital adequacy ratio. This then further negatively affects economic output and impacts back on banks in the form of, for example, increased loan losses. In the main empirical section of the paper, this effect was simulated on the example of the Czech banking sector. The simulation results suggest that under certain assumptions the feedback loop may play an important role.
Keywords: G21; E44; E47; 330; procyclicality; feedback loop; bank regulation; deleveraging; Finanzsektor; Konjunktur; Bankenregulierung; Basler Akkord; Tschechische Republik